Film Licensing Agreement as an Object of Guarantee in Indonesia - Pratama, Muhammad Ath-Thaariq; Abubakar, Lastuti; Handayani, Tri; Sugiharti, Dewi Kania (Trunojoyo Madura University, 2025)
Collateral is part of an agreement as a result of financial obligations and serves to provide confidence that the debtor will fulfil these financial obligations, where the guarantee is something that is submitted to the creditor by the debtor. The guarantee itself is divided into two, namely material security and personal guarantee. The license agreement itself is an agreement made by the license owner and the party who wants to use the license. One of the uses of a license agreement is in the film industry, where the Product House as a license owner can enter into a license agreement with the Video on Demand platform so that the film or series that has been made can be shown on the Video on Demand platform. Government Regulation No. 2022 on Creative Economy has opened up opportunities for license agreements as collateral objects. The license agreement as a collateral object itself is not an impossible thing, because other countries such as Iran and the United States have allowed license agreements as collateral objects. One of the Video on Demand platforms that uses license agreements in the screening of films on their platform is Netflix. Therefore, the Production House can make the license agreement made as an object of collateral.